Biomechanical risk intervention on pain: case study in a printing industry’s offset sector - Righi, Angela Weber; Rodrigues, Leonardo Rocha (Revista Gestão da Produção Operações e Sistemas, 2009)
The presence of risk factors for developing Work Related Occupational Disorders (DORT) is emphasized in several activities. The purpose of this study was to verify the correlation that exists between biomechanical risk and the presence of pain in 18 employees in the offset sector of a printing establishment. The methodology ap- plied was the RULA Method (Rapid Upper Limb Assessment) and Corlett and Bishop’s modified Diagram. Data analysis shows the presence of pain appearing and/or increasing along the workday. It was not possible to cor- relate it with age and work time of the collaborators. The points with larger indications of pain were ankles and feet followed by shoulders, arms and upper back. The biomechanical risk degree revealed an average of 5.21± 1.59 demanding larger investigation and changes soon. It was concluded that according to results achieved by this research, there is a correlation between biomechanical risk and the presence of pain in the offset sector of the printing establishment studied. We suggest the continuity of this study, aiming at a larger investigation on topics found and suggestions for aspects requiring changes, always focusing on the improvement of workers’ occupational health. Keywords: Biomechanical risk; pain; RULA method; printing industry.